O new journalism entre o factual e o ficcional: das aproximações entre literatura e jornalismo - Keske, Humberto Ivan (2024)
The proposal of the present text on literature and journalism: as complementary and not exculpatory areas, aim at to discourse on the approach between both the sorts, being given emphasis when journalistic making. At a first moment, the necessity appears of a brief historical panel, contexting the world of the journalism that, in its origins, counted on the active participation of writers in periodical writings. New journalism appears in this perspective as the first experience of disruption admitted to the traditional squeak of the press, either for the indignation of the conservationism; either for the irreverence in relation to the basic rules of the journalism, as objec-tiving and to moving away of the facts.